A Traditional Aboriginal Condiment as an Antioxidant Agent in the Development of Biodegradable Active Packaging - Guarda-Moraga, A; Bruna-Bugueno, J; Galotto-Lopez, M; Torres-Mediano, A; Lopez de Dicastillo-Bergamo, A; Alvarado-Almonacid, N (John Wiley and Sons Inc., 2017)
In this study, antioxidant food-packaging materials were developed by the incorporation of merkén, an aboriginal Chilean spice, into a biodegradable polymer matrix, poly(lactic acid). Antioxidant activity assays and the phenolic content of merkén showed interesting results compared to other condiments, such as oregano and parsley. Active materials with merkén at 3 and 5 wt % were successfully obtained by extrusion. Chromatographic analysis revealed the chemical composition of merkén, and its active material was based on interesting flavonoids and organic acids, such as catechin, myricetin, and gallic and ellagic acids. Scanning electron micrographs showed that the merkén particles accumulated in aggregates; this resulted in an increase in the permeability values and a reduction in the crystallinity and mechanical properties of the polymer matrix. Nevertheless, these materials presented interesting antioxidant activities as radical scavengers on aqueous food simulants. The kinetics of release was dependent on the type of food and the nominal content of merkén in the films. © 2017 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2017, 134, 44692. © 2017 Wiley Periodicals, Inc.